Exploration of Central Kalimantan’s forest plants as bioactive compound resources - MAE SRI HARTATI WAHYUNINGSIH; SUBAGUS WAHYUONO; DJOKO SANTOSA; JUSAIN SETIADI; SOEKOTJO SOEKOTJO; SITI . MUSLIMAH WIDIASTUTI; RITA RAKHMAWATI; DINAR SARI CAHYANINGRUM WAHYUNI (Society for Indonesian Biodiversity, 2008)
The width of the forest area of Indonesia is about 75% of the entire land which has not been optimally utilized as a raw medicinal resource. The forest area is rich in plants of various medicinal benefits which have not been found out and developed. The aim of the study was to explore Central Kalimantan’s forest plants as bioactive compound resources. Using Brine Shrimp Lethality Test (BST) method the exploration was conducted on 70 kinds of plants which had been traditionally used in that area. The dry powder was macerated inchloroform and then in methanol in order to obtain 140 chloroform and methanol extracts, each 70 extracts respectively. The activities of those extract were tested on 500 dan 1000 μg/mL of their concentration. The result was analized using probit regresion in order to obtain LC50 value. The result of the study indicated that from those 140 extracts, were obtained 70 active extracts (100% dead larva Artemiasalina) in their concentration of 500 μg/mL. Concentration decreasing up to 100 μg/mL produced 10 active extracts (100% dead larva A. salina) which potential developed as bioactive compound resources.© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Central Kalimantan, plant exploration, bioactive compound, Brine Shrimp Lethality Test.